MiR‐375‐mediated suppression of engineered coxsackievirus B3 in pancreatic cells. Issue 4 (7th November 2019) - Pryshliak, Markian; Hazini, Ahmet; Knoch, Klaus; Dieringer, Babette; Tolksdorf, Beatrice; Solimena, Michele; Kurreck, Jens; Pinkert, Sandra; Fechner, Henry
Abstract : Coxsackievirus B3 (CVB3) has potential as a new oncolytic agent for the treatment of cancer but can induce severe pancreatitis. Here, we inserted target sequences of the microRNA miR‐375 (miR‐375TS) into the 5′ terminus of the polyprotein encoding sequence or into the 3′UTR of the CVB3 strain rCVB3.1 to prevent viral replication in the pancreas. In pancreatic EndoC‐βH1 cells expressing miR‐375 endogenously, replication of the 5′‐miR‐375TS virus and that of the 3′‐miR‐375TS virus was reduced by 4 × 10 3 ‐fold and 3.9 × 10 4 ‐fold, respectively, compared to the parental rCVB3.1. In colorectal carcinoma cells, replication and cytotoxicity of both viruses were slightly reduced compared to rCVB3.1, but less pronounced for the 3′‐miR‐375TS virus. Thus, CVB3 with miR‐375TS in the 3′UTR of the viral genome may be suitable to avoid pancreatic toxicity. Abstract :